Polar lipids from wheat extract oil improve skin damages induced by aging: Evidence from a randomized, placebo‐controlled clinical trial in women and an ex vivo study on human skin explant. (29th April 2019) - Boisnic, Sylvie; Keophiphath, Mayoura; Serandour, Anne‐Laure; Branchet, Marie‐Christine; Le Breton, Stéphanie; Lamour, Irène; Gaillard, Emmanuelle
Abstract: Background: Polar lipids from wheat ( Triticum vulgare/aestivum ) extract oil (WEO) are known to improve skin hydration. Aims: These studies aimed to assess WEO benefits on the skin appearance of middle‐aged women. Methods: A double‐blind, randomized, placebo‐controlled clinical study was carried out on 64 healthy women, aged from 45 to 60 years, to investigate antiaging effects and benefits for the skin. The study lasted 20 weeks including 12 weeks of oral supplementation with WEO or placebo and 8 weeks of follow‐up. Wrinkles in the "crow's‐feet" area were evaluated by the Lemperle score. Skin hydration was measured using a corneometer, while roughness and radiance were determined by clinical scoring. Collagen content was quantified in human skin explants exposed to ultraviolet (UV) irradiations and treated with WEO or vehicle control. Results: Compared to the placebo group, the Lemperle score was significantly reduced in the WEO group between W0 and W8 to reach a clinically significant 1 grade at W12. Facial hydration was significantly improved in the WEO group from W0 to W12, whereas leg hydration was significantly increased after 4 weeks and lasted throughout the supplementation period. Skin roughness and radiance were also significantly improved from W0 to W8 in the WEO group compared to placebo group. A higher collagen content was measured in the UV‐irradiated skin explants treated with WEO compared to the untreated ones. Conclusion: These results confirmed the moisturizing effect of WEO and, for the first time, revealed its potential antiaging properties.